Global oil risk price management in Iran and Russia - S. Alikhani (Управление)
Oil is one of the most important sources of income for oil-exporting countries such as the Russian Federation and Iran, as well as the main raw material in the production process in oil-importing countries. Risks fluctuations in world oil prices can cause sovereign financial risks of instability in macroeconomic variables in both groups of oil exporting and importing countries. Negative shocks in world oil prices for countries such as Iran and Russia, whose economic structure is oriented towards oil and provides a significant part of the state budget through oil, could have significant consequences for the economies of these countries. Such fluctuations not only affect the economies of oil-importing countries, but are also one of the main causes of disruptions in the economies of oil-exporting countries. This study examines the government's management of risk fluctuations in world oil prices and its actions in Iran and Russia. The results of this study show that Iran and Russia, as sanctioned countries and oil exporters, have taken various measures to deal with these shocks, the most important of which is the creation of sovereign wealth funds in the two countries. In this article, the characteristics of national development funds in Iran and Russia are compared. The differences between Iran and Russia in risk management and the structure of these funds are shown.